Scientific research and technological development system in Algeria: Current situation And development strategies - Zamouri, Kamel; Merdaoui, Kamel (Milev Journal of Research and Studies, 2017)
This study comes to display an image on the reality of scientific research and technological development in Algeria, the researchers diagnosis of this fact that showed a significant educational network in terms of number of structures and census of students and teachers, and network research arguing in the government and higher education field, but the scientific production and patents in Algeria remains weak in termsof quantity and quality.They also discussed the factors that led Algeria's system of science and technology to the lack of transition to a national system ofinnovation, Algeria is still complaining about the many shortcomings in creating an environment for innovation and creativity, the most important is low private sector spending on research and development, absence ofpartnership and poor cooperation between research institutions in universities and production enterprises and the deterioration of the quality of scientific research institutions. Finally, the researchers designed a future vision to raise the level ofscientific research and technological development in Algeria, maybe the latter make an active and influential in various aspects of community life